Isolation of Galactomannan from tamarind (Tamarindus indica) seed - Erispe, Flordelhyn Carell E.
This study aims to isolate galactomannan from tamarind (Tamarindus indica) seed collected from Magdalena, Anini-y, Antique. The presence of galactomannan in the gum isolate was confirmed using Fourier Transform Infrared (FTIR) spectroscopy. The IR spectra of the gum isolate were compared with the IR spectra of galactomannan extracted from other seed sources namely: Gleditsia triachanthos, Caesalpinia pulcherrima and Adenanthera pavonina. The isolated gum was subjected to different tests. The first test conducted was the solubility test. Solubility of the gum is dependent on the mannose:galactose ratio. The gum isolate from tamarind seeds were insoluble with organic solvents and soluble with inorganic solvents. The isolated gum was partially soluble with hot and cold water. The gum isolate was positive fro Benedict?s test for reducing sugars. The isolated gum was characterized by determining the viscosity and water-holding capacity. The water-holding capacity of the gum isolate was found to be 63.2% and its calculated viscosity was 20.96. The total sugar concentration of the gum was 64.8%. Thin layer chromatography was done to determine the Rf value of the galactomann in the gum isolate and the calculated Rf value was compared with the standard values for galactomann.